(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This socio-discourse research examines diasporic cinema and national identity. Diasporic cinema, which depicts displacement, migration, and cultural hybridity, illuminates how films negotiate national identity in globalized situations. The examination examines how diasporic filmmakers negotiate themes of belonging, memory, and home across cultures using identity formation, cultural representation, and cinematic discourse theories. This study examines diasporic film case studies to explain how cinematic tales shape national identities in a globalized environment. The study adopts a descriptive qualitative approach with the use of models of Van Dijk (2000) and (2006). The data was chosen from different movies such as Citizen (2001), Visitor (2022), Amreeka (2009) and Hologram for The King (2016). The research paper concludes that The film explores national identity, personal identity, and resilience in three socio-discourse levels. In "Amreeka," it highlights national identity amid geopolitical tensions, while "The Citizen" examines the impact of the Green Card Lottery system on immigration and identity. "A Hologram for The King" highlights Middle Eastern social identities, class and social standards, and societal roles. "The Visitors" explores themes of homecoming and beginning over, highlighting migration, culture, and personal history. The text explores various types of diasporas, including Palestine diaspora, Lebanese diaspora, expatriate diaspora, and international diaspora. The Palestinians face challenges in obtaining legal status and citizenship due to 40-year occupation, while the Lebanese diaspora focuses on absorbing American culture. The international diaspora highlights the importance of family ties and global linkages.